Pembelajaran Pendidikan Agama Islam dan Budi Pekerti Berwawasan Multikultural di SMA Negeri 10 Kota Bengkulu - Ach Jainuri (UIN Fatmawati Sukarno Bengkulu, 2023)
The purpose of this study is (1) To find out and describe the implementation of multicultural-based education in Islamic Religious Education and Character Education learning at SMA N 10 Bengkulu City. (2) To find out and describe the strategies of Islamic Religious Education and Character Education teachers in having a multicultural perspective at SMA N 10 Bengkulu City. (3) To find out and describe the obstacles to the implementation of Islamic Religious Education and Character Education learning with a multicultural perspective at SMA N 10 Bengkulu City. The type of research used in this study is descriptive qualitative research, the research subjects who can provide information are the principal or vice principal and teachers. Research results (1) Implementation of Islamic Religious Education and Character Education learning based on multiculturalism for students at SMAN 10 Kota Bengkulu with (a) planning, (b) implementation (c) evaluation (2) Strategy for delivering Islamic Religious Education material based on multiculturalism includes: (a) utilization of learning media, (b) learning messages developed in the learning program are refined annually, in accordance with the existing curriculum, (c) learning materials, (d) learning media, (e) learning materials, and (f) learning is carried out outside the classroom, (3) To achieve a learning objective, there are supporting factors in its implementation. Not only that, in its implementation there will certainly be obstacles that will slow down the achievement of the learning objectives. Among the supporting factors at SMA N 10 Kota Bengkulu are: a) Government policy (curriculum), b) School social environment, c) Facilities and infrastructure. Meanwhile, the inhibiting factors in the implementation of multicultural-based Islamic religious education learning at SMA N 10 Bengkulu City include: a) Students' emotional maturity, b) Students' different understanding of Islamic Religious Education lessons.